Shelf Life Extension of Tomato Paste Through Organoleptically Acceptable Concentration of Betel Leaf Essential Oil Under Accelerated Storage Environment. Issue 5 (16th April 2018) - Basak, Suradeep
Abstract : Abstract: This study was attempted with two objectives: (1) to find an acceptable concentration of betel leaf essential oil (BLEO) based on sensory evaluation that can be employed in tomato paste; (2) to evaluate the effect of the acceptable concentration of BLEO in the paste during accelerated storage under 89 ± 1.2% RH at 39 ± 1 °C. Linguistic data obtained from sensory evaluation of tomato paste treated with 4 different concentrations of BLEO were analyzed using fuzzy logic approach. The organoleptically acceptable concentration was determined to be 0.25 mg/g of BLEO in tomato paste. The effect of the selected concentration of BLEO on different physicochemical and microbial attributes of tomato paste during accelerated storage was studied. Untreated tomato paste was found to have 12% less total antioxidant capacity than treated paste at the end of storage. Based on a * / b * value in CIELAB color space, the BLEO treated paste efficiently extended the shelf life by 14 days with respect to untreated paste samples under accelerated storage conditions. BLEO comes with a tag contributing to green consumerism, and its application as food preservative is no less than a value addition to the product. Practical Applications: Essential oil is considered to have promising potential as an alternative food preservative, and its use is practically possible if they could overcome the sensory barrier, while retaining the preservative potency. The importance of identifying the sensory attributes for commercial success of essential oil treated food product was considered in this study. It contributes to the potency of organoleptically acceptable concentration of BLEO in shelf life extension of tomato paste under accelerated storage conditions. At industrial level, the estimated shelf life of treated tomato paste can be increased by incorporating more hurdles alongside BLEO.